2023
DOI: 10.1037/hea0001272
|View full text |Cite
|
Sign up to set email alerts
|

Do optimism and moralization predict vaccination? A five-wave longitudinal study.

Abstract: Objective: To examine if personal and comparative optimism, perceived effectiveness, and moralization of vaccination predict people's decision to get vaccinated. Methods: We measured self-reported vaccination decisions in a five-wave longitudinal study (N ≍ 5,000/wave) in Belgium over a six months period (December 2020–May 2021) during the COVID-19 pandemic. Among the predictors were demographic factors, personal and comparative optimism for three aspects of COVID-19 (infection, severe disease, good outcome), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…However, these results were heterogeneous; individuals with baseline antivaccine attitudes demonstrated a reduction in willingness to be vaccinated against COVID-19 after seeing the positively framed messages, suggesting that tailoring this approach should incorporate awareness of baseline vaccine attitudes, a similar finding to prior work concerning messaging for routine childhood vaccination (Nyhan et al, 2014). Delporte et al (2023) conducted a five-wave study in Belgium that focused on measures of optimism as a whole, referred to by the authors as "personal" (e.g., "better things are more likely to happen than worse, in general") and in a "comparative" fashion ("better things are more likely to happen than worse, for me rather than others"). "Personal" optimism was more salient for older respondents who may have a greater perception of individual risk, and "comparative" optimism was more salient for younger respondents.…”
Section: Overview Of the Special Issuementioning
confidence: 88%
See 3 more Smart Citations
“…However, these results were heterogeneous; individuals with baseline antivaccine attitudes demonstrated a reduction in willingness to be vaccinated against COVID-19 after seeing the positively framed messages, suggesting that tailoring this approach should incorporate awareness of baseline vaccine attitudes, a similar finding to prior work concerning messaging for routine childhood vaccination (Nyhan et al, 2014). Delporte et al (2023) conducted a five-wave study in Belgium that focused on measures of optimism as a whole, referred to by the authors as "personal" (e.g., "better things are more likely to happen than worse, in general") and in a "comparative" fashion ("better things are more likely to happen than worse, for me rather than others"). "Personal" optimism was more salient for older respondents who may have a greater perception of individual risk, and "comparative" optimism was more salient for younger respondents.…”
Section: Overview Of the Special Issuementioning
confidence: 88%
“…The other 11 papers in this special issue present novel research findings across a wide range of aspects of health psychology and vaccination practice. Most of them focus exclusively on COVID-19 (Bogg et al, 2023; Buscemi et al, 2023; Delporte et al, 2023; Eberhardt and Ling, 2023; Husted et al, 2023; Ku et al, 2023; Martin et al, 2023; Preis et al, 2023; Warren et al, 2023), but others concern influenza (Bender et al, 2023; Brumbaugh et al, 2023) and HPV vaccines (Brumbaugh et al, 2023). Six of the research articles (Bogg et al, 2023; Brumbaugh et al, 2023; Buscemi et al, 2023; Martin et al, 2023; Preis et al, 2023; Warren et al, 2023) report on studies conducted in the United States, while two (Eberhardt and Ling, 2023; Husted et al, 2023) were conducted in the United Kingdom, one (Bender et al, 2023) in Germany, one (Delporte et al, 2023) in Belgium, and one (Ku et al, 2023) in South Korea.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
See 2 more Smart Citations
“…shown that moralizing preventive measures against diseases (e.g., vaccination) may reduce rather than enhance people's willingness to comply with them (e.g., Delporte et al, 2023;Kraaijeveld & Jamrozik, 2022). Therefore, more seems to be gained of presenting precautions against COVID-19 as having instrumental (vs. moral) value.…”
Section: Discussionmentioning
confidence: 99%